Copper cobalt spinel as a high performance cathode for intermediate temperature solid oxide fuel cells. Issue 55 (21st June 2016) - Shao, Lin; Wang, Qi; Fan, Lishuang; Wang, Pengxiang; Zhang, Naiqing; Sun, Kening
Abstract : CuCo2 O4 spinel prepared via an EDTA–citric acid process was studied as a candidate solid oxide fuel cell (SOFC) cathode material at intermediate temperatures (IT). Abstract : CuCo2 O4 spinel prepared via an EDTA–citric acid process was studied as a candidate solid oxide fuel cell (SOFC) cathode material at intermediate temperatures (IT). CuCo2 O4 cathodes were measured using thermal gravimetric analysis, X-ray diffraction and scanning electron microscopy. AC impedance spectroscopy and DC polarization measurements were used to study the electrode performance. The obtained value of the polarization resistances at 800 °C was 0.12 Ω cm 2 with a maximum power density of 972 mW cm −2 .